Analys och design av komponenter till SBU 8000 med rotator - Forslund, Johan (2013)
This report describes a master thesis for a Master of Engineering exam with focus on mechanical engineering and design at Luleå University of Technology, LTU. The thesis is performed in collaboration with Jama Mining Machines AB by Johan Forslund, partly located in Skelleftehamn and partly at the University. The goal is to increase the strength of two of Jama Mining Machines components found in the boom of the scaler SBU 8000 with rotator. The strength is increased by changing the design of the specific components. An analysis of the current situation for the current design is carried out to identify the necessary improvements for the new design. The development of the new design uses a structural product development process that is inspired by Ulrich & Eppinger. To verify the improvement of the new design strength static calculations by the finite element method is used in SolidWorks, a Computer Aided Design program. The forces used in the calculations is only a theoretical approximation, no experiments are conducted to describe the correct forces. Therefore are the stresses that are presented in the report not the real stresses that are reflected in the components. The calculations are instead used for comparisons between the current design and the new concepts from the product development process. The increased strength of the new design is verified as a percental decrease of the maximum stress compared with the current design. The final concepts design is developed at detailed level and presented to Jama Mining Machines as a proposition on manufacturing drawings for the new design of the specific components. Validerat; 20130820 (global_studentproject_submitter)